(untitled) (Research, Society and Development, 2020)
The objective was to carry out lamb carcass evaluation in a confinement system fed with 100% concentrated diet and diet with the inclusion of residual oil, in order to identify which diet provides the best performance. Fifteen male sheep, not castrated, crossbred from Dorper × Santa Inês, aged six months, confined in collective pens for 50 days were used. The treatments were as follows: Control Diet (TC) - Tifton hay + concentrate; High grain diet (AG) - 100% commercial diet for sheep; Diet with residual frying oil (ORF) - Tifton hay + concentrate + residual frying oil. Morphometric measurements were collected weekly during the confinement period: withers height, croup height, chest circumference and body length for carcass evaluation. There was no statistical difference for dry matter consumption, weight gain, croup height, withers height, body length, chest circumference, carcass yield, carcass weight, carcass patella perimeter, carcass shank length and perimeter carcass shank (P> 0.05) between the control diet and inclusion of 6% residual oil. Although it does not differ statistically from the control diet, the inclusion of residual oil promoted superior dry matter consumption, total weight gain, hot and cold carcass weight and hot carcass thoracic perimeter in relation to animals fed a high grain diet. The diet with inclusion of 6% of residual oil provided better productive results and performance to the lambs.